Textbook on socio economic offences - Gaur, K D (Gurgaon Universal, 2022)
Textbook on socio-economic offences is divided into two separate categories of offences viz., social and economic offences. Social offences are those which affect the wealth or material welfare of the community as a whole and not merely individual victim.
Keywords: Socio economic